Incidence of Post Operative Wound Infection Following the Use of Antibiotics in Clean Contaminated Head and Neck Surgery in a Tertiary Care Centre in Eastern Nepal - Chapagain, K.; Pokharel, R.; Acharya, R.; Shah, S.; Paranjape, B.D. (Birat Journal of Health Sciences, 2017)
Introduction Post operative wound infection continues to be the major concern even after the appropriate antibiotic coverage. Objective To find out the incidence of post operative wound infection following the use of antibiotics in clean contaminated head and neck surgery in a tertiary care centre in Eastern Nepal. Methodology It is a prospective study conducted at Department of Otorhinolaryngology and Head and Neck Surgery, Nobel Medical College Teaching Hospital, Biratnagar from 14th April 2013 to 12th April 2015. Patient who underwent clean contaminated head and neck surgery were followed up on 1st, 3rd and 6th post–operative day (POD) and wounds were inspected for any signs of wound infection. Results A total of 144 patients undergoing various clean contaminated head and neck surgeries were included in this study. Tonsillectomy was the commonest surgery performed (40.27%). An overall wound infection rate was 11.80%. Serous discharge rd from the surgical site observed on 3rd post operative day was the most common presentation of wound infection (29.41%). Parotidectomy was the surgery presenting with highest rate of wound infection (31.25%). Conclusion This study concludes that even the best technique and appropriate antibiotic has not completely eliminated the problem of wound infection in clean contaminated head and neck surgery. Birat Journal of Health Sciences 2016 1(1): 51-55